Investigation into evaluation of agriculture informatization level based on two-tuple - Liu, Peide; Zhang, Xin (Technological and Economic Development of Economy, 2011)
Agriculture informatization level is an important part of one country's modernization. It is important to construct reasonable agriculture informatization evaluation indicator system and propose the evaluation method for promoting the agriculture informatization. This paper firstly analyzes the research status of the indicator system and evaluation method of informatization at home and abroad. On the basis of the relative literatures, the evaluation indicator system of the agriculture informatization in China is constructed, and the evaluation model of the agriculture informatization based on two-tuple and the relative operators are also constructed. This model not only can be used to rank the orders of the different areas according to the informatization level, but also can realize the qualitative evaluation of the agriculture informatization of the different areas according to the evaluation system. Finally, the application example shows that the evaluation system of the agriculture informatization constructed in this paper is effective, and the evaluation method proposed in this paper is simple and easy to use.